2007
DOI: 10.2307/25549733
|View full text |Cite
|
Sign up to set email alerts
|

Is Poverty a Driver for Risky Sexual Behaviour? Evidence from National Surveys of Adolescents in Four African Countries

Abstract: This paper contributes to conflicting evidence on the link between poverty and risky sexual behaviour by examining the effect of wealth status on age at first sex, condom use, and multiple partners using nationally representative adolescents' data from Burkina Faso, Ghana, Malawi, and Uganda. The results show that the wealthiest girls in Burkina Faso, Ghana, and Malawi had later sexual debut compared with their poorer counterparts but this association was not significant for Uganda. Wealth status was weaker am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
88
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 23 publications
(30 reference statements)
11
88
6
Order By: Relevance
“…Although income as an indicator for measuring socioeconomic status is associated with some inaccuracies such as reporting biases, seasonal nature of incomes in agricultural economies and rapid inflation it is often used to assess socio-economic or wealth status (Ghana Statistical Service 2000Doocy and Burnham 2006;Madise et al 2007;Vyas and Kumaranayake 2008). The total sample size of 299 (both migrants and indigenes) was ranked into five quintiles on the basis of total monthly household income as reported by the respondents (Gwatkin et al 2000).…”
Section: Assessment Of Household Incomementioning
confidence: 99%
“…Although income as an indicator for measuring socioeconomic status is associated with some inaccuracies such as reporting biases, seasonal nature of incomes in agricultural economies and rapid inflation it is often used to assess socio-economic or wealth status (Ghana Statistical Service 2000Doocy and Burnham 2006;Madise et al 2007;Vyas and Kumaranayake 2008). The total sample size of 299 (both migrants and indigenes) was ranked into five quintiles on the basis of total monthly household income as reported by the respondents (Gwatkin et al 2000).…”
Section: Assessment Of Household Incomementioning
confidence: 99%
“…The qualitative interviews with young people and adults in the present study-which revealed young peoples' feelings, fears, shyness, and dilemmas regarding protected and unprotected sex, condom use, and premarital sexual abstinence-contribute to a better understanding of their premarital sexual behavior. Understanding the influencing factors that motivate young males and females to have protected or unprotected sex, and understanding these factors in specific contexts, can contribute to the development of more tailored and effective SRH education to protect young people from the adverse consequences of engaging in unprotected sex (Darteh et al 2014;Karim et al 2003;Madise et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…This insight could contribute to the development of more tailored and effective sexual and reproductive health (SRH) programs to protect young males and females from the adverse consequences of having sex without contraceptive methods (Darteh et al 2014;Karim et al 2003;AwusaboAsare and Annim 2008;Madise et al 2007).…”
mentioning
confidence: 99%
“…Results of the study in Nairobi showed that people in slum area started to commit sexual intercourse at the earlier age had more sexual partners and be less active to determine or take preventive ways from HIV/AIDS transmission. 6,22 …”
Section: Discussionmentioning
confidence: 99%